Comparison of CIDR to MGA in a 7-11 cosynch protocol with timed insemination of beef heifers - Eborn, D.R.; Freneau, G.E.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Previous research has shown that the 7-11 Cosynch protocol using melengestrol acetate (MGA) is effective in synchronizing beef heifers. This study compared MGA and a vaginal insert containing progesterone (CIDR) in the 7-11 Cosynch protocol on beef heifers. Replacement beef heifers (n=179) from three herds were assigned to MGA or CIDR treatments. Beginning on day 1, heifers on the MGA treatment were fed to consume 0.5 mg daily of MGA for 7 days. On day 7, the last day of MGA feeding, the MGA heifers received an injection of Lutalyse (PGF). Heifers on the CIDR treatment received a CIDR on day 3; on day 9 the CIDR was removed, and heifers received an injection of Lutalyse. On day 11, all heifers received an injection of OvaCyst (gonadotrophin-releasing hormone; GnRH), followed by another injection of Lutalyse® 7 days later (day 18). At 48 hours after the final Lutalyse injection, all heifers were time inseminated and received an injection of OvaCyst. Pregnancy status was determined 33 days after breeding by ultrasonography. No difference in pregnancy rate was observed between the CIDR (46%) and MGA (47%) treatments.
Keywords: Beef; CIDR; MGA; 7-11 cosynch; Heifers